INFLUENCE OF PRODUCT QUALITY AND SERVICE QUALITY ON PIZZA HUT CUSTOMER SATISFACTION MEDIATED BY PURCHASE DECISION - Nirmala Sindi Tatia; Barkah Barkah; Bintoro Bagus Purmono; Heriyadi Heriyadi; Pramana Saputra (Jurnal Ekonomi, 2023)
Pizza Hut is a well-known name among enthusiasts of pizza, with its presence in Indonesia dating back to 1958. The intensifying competition in this industry, spurred by the emergence of new competitors, necessitates a thorough examination. This research aims to analyze the influence of product quality and service quality on customer satisfaction, mediated by the purchasing decisions made at Pizza Hut. Data collection employed a questionnaire distributed to 225 respondents using purposive sampling techniques. The research adopts a quantitative approach, employing Structural Equation Modeling (SEM) with the assistance of AMOS 24 to analyze and evaluate the measurement and structural models constructed for the study. The findings of this research reveal a positive and significant influence of product quality and service quality on purchase decisions. Both product quality and service quality exert a positive and significant impact on customer satisfaction. Purchase decisions significantly influence customer satisfaction in a positive manner. Furthermore, product quality and service quality positively and significantly influence customer satisfaction through purchase decisions.